INFECCION POR EL VIRUS DEL PAPILOMA HUMANO. BIOLOGIA MOLECULAR - Vega-Malagón, Genaro; Ávila-Morales, Javier; García-Solís, Pablo; Camacho-Calderón, Nicolás; Becerril-Santos, Alma; Malagón, Alfredo Jesús Vega; Leo-Amador, Guillermo E. (European Scientific Journal, ESJ, 2014)
The human papillomavirus (HPV ) , is important because it is the sexually transmitted disease more common , worldwide, to be associated with cervical cancer , all therapeutic modalities have a high recurrence rate and probably not eradicated . With advances in molecular biology , diagnosis and classification have changed their treatment. HPVs are icosahedral structures of 55 microns in diameter with a dense central core DNA , a protein capsule surrounding him . The HPV DNA is double- band and is in the form of closed loop , with 800 bp are epitheliotropic viruses, genomes of HPV is divided into early ( E ) and late regions ( L ) of the latter encoding structural proteins , and the genes of the first encode proteins required for replication . The genome of certain human papillomavirus is present in most cervical tumors products of viral oncogenes E6 and E7 products inactivate the suppressor genes p53 and Rb . E6 binds to the p53 suppressor protein , resulting in loss of function , the E7 binds Rb retinoblastoma gene. P53 controls the progression of resting cells to growth. Damage to the cell genome p53 levels rise and inhibit this progression . This allows DNA repair before replication , cells lose this control replicate its damaged DNA , which generates genomic instability , the E6 protein of high-risk HPV interacts with p53 and induces its degradation. In cervical lesions expressing E6 and E7 oncogenes could contribute to cellular genomic instability and alterations that accumulate would take to tumor development .